Application of the Boston Technical Performance Score to intraoperative echocardiography. Issue 3 (September 2019) - Bellsham-Revell, Hannah R; Deri, Antigoni; Caroli, Silvia; Durward, Andrew; Miller, Owen I; Mathur, Sujeev; Saundankar, Jelena; Anderson, David R; Austin, B Conal; Salih, Caner; Pushparajah, Kuberan; Simpson, John M
Abstract : Background: The Technical Performance Score (TPS) developed by Boston Children's Hospital showed surgical outcomes correlate with adequacy of technical repair when implemented on pre-discharge echocardiograms. We applied this scoring system to intraoperative imaging in a tertiary UK congenital heart surgical centre. Methods: After a period of training, intraoperative TPS (epicardial and/or transesophageal echocardiography) was instituted. TPS was used to inform intraoperative discussions and recorded on a custom-made database using the previously published scoring system. After a year, we reviewed the feasibility, results and relationship between the TPS and mortality, extubation time and length of stay. Results: From 01 September 2015 to 04 July 2016, there were 272 TPS procedures in 251 operations with 208 TPS recorded. Seven patients had surgery with no documented TPS, three had operations with no current TPS score template available. Patients left the operating theatre with TPS optimal in 156 (75%), adequate 34 (16%) and inadequate 18 (9%). Of those with an optimal score on leaving theatre, ten had more than one period of cardiopulmonary bypass. All four deaths <30 days after surgery (1.9%) had optimal TPS. There was a statistically significant difference in extubation times in the RACHS category 4 patients (3 days vs 5 days, P  < 0.05) and in PICU and total length of stay in the RACHS category three patients (2 and 8 days vs 12.5 and 21.5 days respectively) if leaving theatre with an inadequate result. Conclusions: Application of intraoperative TPS is feasible and provides a way of objectively recording intraoperative imaging assessment of surgery. An 'inadequate' TPS did not predict mortality but correlated with a longer ventilation time and longer length of stay compared to those with optimal or adequate scores.